1989
DOI: 10.1111/j.1745-4565.1989.tb00529.x
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Analysis of Grasses and Legumes Growing on Soil Covering Coal Fly Ash Landfill Sites

Abstract: Forage grasses and legumes growing in the soil covering four coal fly ash landfill sites in Central New York were sampled and analyzed for 20 elements. Selenium, boron and molybdenum were most consistently higher in concentration in these crops than the corresponding control plants sampled from adjacent upwind locations. Legumes absorbed greater amounts of these elements than grasses probably owing to their deep‐rooted penetration of the fly ash layer below. Factors affecting the extent of absorption of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…As a probable consequence of the alkaline substrate, Cu:Mo ratios in the same plant species were below values reported to cause chronic toxicity symptoms in ruminants. Weinstein et al (1989) and Woodbury et al (1999) found Mo concentrations of up to 28.9 mg kg −1 in sweet clover and 18.7 mg kg −1 in bird's foot trefoil ( Lotus corniculatus ), respectively. In both cases, concentrations exceeded values indicating toxicity to animals (Adriano, 2001).…”
Section: Exposure Pathways From Ccr Disposal Sitesmentioning
confidence: 95%
“…As a probable consequence of the alkaline substrate, Cu:Mo ratios in the same plant species were below values reported to cause chronic toxicity symptoms in ruminants. Weinstein et al (1989) and Woodbury et al (1999) found Mo concentrations of up to 28.9 mg kg −1 in sweet clover and 18.7 mg kg −1 in bird's foot trefoil ( Lotus corniculatus ), respectively. In both cases, concentrations exceeded values indicating toxicity to animals (Adriano, 2001).…”
Section: Exposure Pathways From Ccr Disposal Sitesmentioning
confidence: 95%
“…Addition of CFA up to 8% in acidic soils increased yield of several agronomics crops ). CFA addition to soils has increased crop yield of alfalfa (Medicago sativa), barley (Hordeum vulgare), Bermuda grass (Cynodon dactylon), and white clover (Trifolium repens) and improved the physical and chemical characteristics of the soil Weinstein et al 1989). In a previous study, it was reported that mixed application of CFA and paper factory sludge caused appreciable change in soil physical and chemical properties, increased pH, and increased rice (Oryza sativa) crop yield (Hill and Lamp 1980;Molliner and Street 1982).…”
Section: Influence Of Csa As a Soil Amendment In Red Soil For Komatsumentioning
confidence: 99%
“…Nonlandfill vegetation was collected from areas adjacent to the landfill. Each replicate was a composite sample of approximately 25 plants of each species, collected along a transect [10,16]. There were three replicates of each species at each site.…”
Section: Experimental Designmentioning
confidence: 99%